Peran Konsep Diri Terhadap Penguasaan Kompetensi Keperawatan Gawat Darurat Pada Mahasiswa Keperawatan di Indonesia - Yektiningsih, Erwin; Zulvana; Risnasari, Norma; Suryaningsih , Yeni; Rahayu, Dwi (Jurnal Keperawatan Florence Nightingale, 2024)
During education, nursing students need a positive self-concept as a psychological condition as an internal motivation to encourage the formation performance professionals in emergency nursing competencies. The development of self-concept in role component includes individual perceptions ability, and self-confidence has an impact commencement of self-awareness to a professional role in nursing care in emergency work environment adequately. This study aimed analyze correlation between the role of self-concept and emergency nursing competencies to nursing students in Indonesia. Research method used a quantitative approach cross-sectional design with samples of 576 people. Data collection was a questionnaire covering the role of the professional concept self nursing and emergency nursing competencies assessment based on Association of Nursing Vocational Education Institutions Indonesian and  Association of Indonesian Nursing Education Institutions. This study results showed a significant correlation with p value 0.000 (r = 0.534**). This study will provide implications development nursing curricula in Indonesia and emphasize more aspect developing mental readiness of self-concept as an integral part of nursing education, counselling, intensive training, and providing constructive feedback with professional guidance can contribute to increasing student readiness in facing challenges emergency nursing clinical practice.